2023
DOI: 10.1002/jsfa.12760
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation delays tomato (Solanum lycopersicum) ripening by inducing transcriptional changes

Abstract: BACKGROUNDTomato (Solanum lycopersicum) has a relatively short shelf life as a result of rapid ripening, limiting its transportability and marketability. Recently, gamma irradiation has emerged as a viable method for delaying tomato fruit ripening. Although few studies have shown that gamma irradiation delays the ripening of tomatoes, the underlying mechanism remains unknown. Therefore, the present study aimed to examine the effects of gamma irradiation on tomato fruit ripening and the underlying mechanisms us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
(142 reference statements)
1
1
0
Order By: Relevance
“…The browning reaction in KOMs is accelerated by the production of enzymes such as tyrosinase and polyphenol oxidase (Fernandes et al, 2012). In our previous research on tomatoes, after ionising radiation treatment, transcriptome analysis revealed the activation of genes related to DNA repair and the downregulation of genes associated with other biological processes, including enzyme synthesis, which could be relevant to our current results (Yoon et al, 2023). Furthermore, the microbial analysis results depicted the inhibition of the growth of Pseudomonas spp., a browning-related factor, in the KOMs (Table 1).…”
Section: Examination Of Ebi Effects On Browning In Kom During Storagesupporting
confidence: 77%
See 1 more Smart Citation
“…The browning reaction in KOMs is accelerated by the production of enzymes such as tyrosinase and polyphenol oxidase (Fernandes et al, 2012). In our previous research on tomatoes, after ionising radiation treatment, transcriptome analysis revealed the activation of genes related to DNA repair and the downregulation of genes associated with other biological processes, including enzyme synthesis, which could be relevant to our current results (Yoon et al, 2023). Furthermore, the microbial analysis results depicted the inhibition of the growth of Pseudomonas spp., a browning-related factor, in the KOMs (Table 1).…”
Section: Examination Of Ebi Effects On Browning In Kom During Storagesupporting
confidence: 77%
“…Furthermore, these techniques possess the ability to inhibit respiration in fruits and vegetables, which in turn prolongs their shelf-life (Singh et al, 2016). Previous research has evidenced that gamma irradiation induces DNA damage in post-harvest tomatoes by upregulating genes involved in DNA repair and replication and downregulating those associated with respiration and enzyme production (Yoon et al, 2023).…”
Section: Introductionmentioning
confidence: 99%